Lean warehousing optimization in the peruvian plastic sector: reducing returns and costs - Pineda Moreno, Ana Milagros (2024)
The plastic products sector in Peru plays a crucial role as a strategic ally for various industries, due to the versatility of plastic products in multiple applications. However, it faces significant challenges, including a high order rate. This generates considerable economic losses and affects operational efficiency. Warehouse management with Lean techniques, particularly Lean Warehousing, has shown potential to improve operational efficiency and reduce waste, although its application in the warehouse context requires further research. One of the pressing problems of the sector is inefficient inventory management and order preparation, resulting in delays and errors in deliveries. This study proposes a warehouse management model based on Lean tools such as Value Stream Mapping (VSM) principles, slotting and visual control, with the aim of reducing the return rate and improving warehouse management efficiency. Key findings from the research show a significant reduction in the order return rate, from 19.02% to 9.33%, and an improvement in operational efficiency with a 6.07% increase in the order fulfilment rate. Furthermore, the implementation of Lean Warehousing led to a 9.69% reduction in operational costs and a 12% increase in warehouse productivity. The academic impact of this research is reflected in the contribution to the body of knowledge on the application of Lean techniques in warehouse management, while the socio-economic impact includes an improvement in the competitiveness of companies in the plastics sector and a reduction in operational costs, benefiting both companies and the end consumer. The adoption of these practices can result in significant improvements in the operational efficiency and economic sustainability of companies.